2016
DOI: 10.5527/wjn.v5.i6.489
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in hemodialysis patients

Abstract: Infection is a common complication and is the second leading cause of death in hemodialysis patients. The risk of bacteremia in hemodialysis patients is 26-fold higher than in the general population, and 1/2-3/4 of the causative organisms of bacteremia in hemodialysis patients are Gram-positive bacteria. The ratio of resistant bacteria in hemodialysis patients compared to the general population is unclear. Several reports have indicated that hemodialysis patients have a higher risk of methicillin-resistant Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 55 publications
3
53
1
3
Order By: Relevance
“…The most reported microorganisms in CRBSI are Gram-positive organisms of the skin. 13 In some parts of the world catheter related infection caused by Gram-negative organisms. 14 4 The immune deficient patients are more prone for Candida fungal infection of their central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…The most reported microorganisms in CRBSI are Gram-positive organisms of the skin. 13 In some parts of the world catheter related infection caused by Gram-negative organisms. 14 4 The immune deficient patients are more prone for Candida fungal infection of their central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…7 Treatment options for the situation described would include bypass of the thrombosed cephalic vein from the brachial artery to most proximal site of the thrombus; but in this case the thrombus extended as far as the left subclavian vein. 8 In cases of central occlusion, endovascular thrombolysis techniques can be used in acute cases with low doses of urokinase, tissue plasminogen activator (tPA), combined with thromboaspiration or stent angioplasty, when there is central stenosis or cephalic arch stenosis causing hypertension. 9 These techniques offer good results when early signs of access failure are detected, which probably could have occurred with the case described before the outcome of complete and extended thrombosis of the cephalic vein.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of MRSA bacteremia in Canada, Australia, and Scandinavia has increased in the span of 2000 and 2008 (P = 0.035) owing to rise in community-acquired infections (P = 0.013) [4]. The study conducted by Suzuki et al showed that MRSA attributed to 26% of the infections among 42,857 general population in North America and 19.5% of the infections among 26,613 general population in Europe [5].…”
Section: Prevalencementioning
confidence: 99%